Diseño de un Plan estratégico para la empresa "System Technology". - Tipán Toaquiza, Édison Javier (2023)
The present research addresses the challenge of enhancing the efficiency and competitiveness of System Technology company. Commencing with a comprehensive analysis of its current situation, strengths, weaknesses, opportunities, and threats impacting its performance and market positioning were identified. The overall objective was to develop a robust strategic plan that provides a clear vision and guides efforts toward sustainable growth and competitiveness. The methodology employed encompassed thorough research, SWOT analysis, and the definition of SMART objectives to steer the strategy. Specific strategies were proposed in key areas such as human resources, administrative control, organizational change, and staff training. As a result of implementing these strategies, significant improvements in operational efficiency, customer satisfaction, and adaptability to changes in the business environment are expected. Increased productivity and internal talent retention are anticipated. Thus, this work provides a comprehensive approach to optimizing System Technology's organization, highlighting the importance of a solid strategic diagnosis and the implementation of functional methods. These actions seek to achieve sustainable growth and competitiveness in the market.